Particulate matter and the airway epithelium: the special case of the underground?. (25th September 2019) - Cooper, Dawn M.; Loxham, Matthew
Airborne particulate matter (PM) is a leading driver of premature mortality and cardiopulmonary morbidity, associated with exacerbations of asthma and chronic obstructive pulmonary disease, idiopathic pulmonary fibrosis, and lung cancer. The airway epithelium, as the principal site of PM deposition, is critical to the effects of, and initial response to, PM. A key mechanism by which PM exerts its effects is the generation of reactive oxygen species (ROS), inducing antioxidant and inflammatory responses in exposed epithelial cells. However, much of what is known about the effects of PM is based on research using particulates from urban air. PM from underground railways is compositionally highly distinct from urban PM, being rich in metals associated with wheel, rail and brake wear and electrical arcing and component wear, which endows underground PM with potent ROS-generating capacity. In addition, underground PM appears to be more inflammogenic than urban PM in epithelial cells, but there is a lack of research into effects on exposed individuals, especially those with underlying health conditions. This review summarises current knowledge about the effects of PM on the airway epithelium, how the effects of underground PM may be different to urban PM and the potential health consequences and mitigation strategies for commuters and workers in underground railways. Airborne particulate matter in underground railways is much more concentrated and metal-rich than that found above ground. The evidence surrounding what this might mean for effects on the airways of exposed commuters and staff is limited and inconsistent. http://bit.ly/2KtcorT